Reframing Women’s Football through Digital Journalism: The Case of kumparanBOLANITA in Indonesia - A'yuni, Nesia Qurrota (JURNAL KOMUNIKASI INDONESIA, 2025)
The global rise of women’s football has opened new opportunities for media industries worldwide, including in developing countries such as Indonesia. In response to this trend, Kumparan launched kumparanBOLANITA in 2023, the country’s first digital media channel dedicated to women’s football. Drawing on media economy theory, this study examines how globalization, regulation, technology, and audiences shape the dynamics of kumparanBOLANITA as both a corporate social responsibility (CSR) initiative and a strategic move within Indonesia’s media ecosystem. Employing a qualitative case study approach, data were collected through interviews, document analysis, and observations, including insights from editorial team managing the channel. Findings show that kumparanBOLANITA has significantly raised public awareness of women’s football, as reflected in the growing participation of grassroots football schools and high audience engagement with national women’s team coverage – sometimes exceeding that of men’s football content. Nonetheless, the platform faces persistent challenges, including the scarcity of consistent competitions to generate news, social stigma surrounding women’s participation in football, and the volatility of digital audiences in a highly competitive market. Overall, kumparanBOLANITA exemplifies how digital media can harness global momentum and local initiatives to foster inclusivity and support the growth of women’s football in Indonesia.